DETERMINANT FACTORS OF PROFIT GROWTH : EMPIRICAL STUDY ON MINING COMPANIES IN INDONESIA - Rahmawai Hanny Yustrianthe (Universitas Tidar, 2022)
Profit growth is an increase or decrease in company profits in a certain period. This study aims to determine the effect of the current ratio, debt to equity ratio, net profit margin, return on assets, and total asset turnover on profit growth in mining companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The population in this study are mining companies listed on the Indonesia Stock Exchange as many as 49 companies. Sample selection was carried out using purposive sampling method so that 38 companies were obtained as samples. The type of data used in this study is secondary data obtained from the Indonesia Stock Exchange (IDX) and the company's official website. The analytical method used is multiple linear regression analysis. The results of this study indicate that the current ratio, debt to equity ratio, net profit margin, and return on assets have a significant effect on profit growth. Meanwhile, total asset turnover has no significant effect on profit growth in mining companies listed on the Indonesia Stock Exchange for the 2016-2020 period